A polyurethane composite material for multi-use comfort shoes and preparation method thereof
By using solid ball shear thickening liquid capsules and hollow ball expandable beads in polyurethane foam for two-phase enhancement, the problem of insufficient mechanical properties and energy absorption efficiency of polyurethane foam shoes is solved, and higher mechanical properties and energy absorption efficiency are achieved, extending service life and improving comfort.
Patent Information
- Application Number
- CN202310182404.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-01
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-03-01
AI Technical Summary
The existing polyurethane foam shoe materials have insufficient mechanical properties and energy absorption efficiency under the conditions of maintaining low density, resulting in short service life and poor comfort.
Solid ball shear thickening liquid capsules and hollow ball expandable beads are used to enhance the polyurethane foam in both phases, regulate the cell structure, and improve the mechanical properties and energy absorption efficiency of the composite material.
While maintaining the apparent density basically unchanged, the mechanical properties and energy absorption efficiency of polyurethane composites are significantly improved, stress sensitivity and damping effects are enhanced, service life is extended and comfort is improved.
Smart Images

Figure CN116178781B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polyurethane composite material for multi-use comfort shoes and a preparation method thereof, belonging to the technical field of polyurethane composite materials. Background Art
[0002] Polyurethane foam is a block copolymer elastomer with soft and hard segments connected by urethane bonds (—NHCOO—). It is a polymer material with light weight, cushioning, heat preservation and other characteristics. Shoes made of polyurethane foam have good properties, such as light weight, impact resistance, chemical resistance, wear resistance and bending resistance. In order to achieve the effect of light weight, one of the conventional methods to reduce the density of polyurethane foam is to use water as a foaming agent, but the introduction of water will lead to an increase in urea bonding and destroy the mechanical properties of the substrate. The foam material will produce stress softening during the cyclic compression process, shortening the service life of the shoe material. Therefore, mechanical properties are also a focus of polyurethane composite materials for shoes.
[0003] With the rapid economic development and the accelerated pace of life, people's requirements for shoes are not only comfortable, but also long service life and multifunctionality, that is, they must meet the needs of different usage scenarios and different user groups for shoes. The resilience of polyurethane shoe materials comes from the compression and release of their pore structure. Generally, flexible polyurethane foam materials are mostly uniform open-cell structures. When slightly compressed, they can achieve dimensional recovery due to their material strength. However, when the external load is large, the pore structure breaks, reducing the material's dimensional stability and recovery ability as well as energy absorption efficiency. Therefore, energy absorption efficiency is also one of the important concerns of polyurethane composite materials for shoes.
[0004] Under the condition of keeping low density, strengthening polyurethane foam can improve the application range of polyurethane foam for shoe materials. The main methods are: adding heat-expandable microspheres, adjusting the proportion and functionality of polyols, optimizing the configuration of cross-linking agents, and adding shear thickening materials. Among them, adding heat-expandable microspheres is the simplest and cheapest, and does not increase or decrease the density.
[0005] Hollow spherical expandable beads are heat-expandable microspheres. The outer layer is a thermoplastic resin with good gas barrier properties. It is generally a core-shell material formed by homopolymerization or copolymerization of monomers such as vinyl chloride, acrylonitrile, and methacrylonitrile. When the temperature rises to a certain level, the polymer layer will soften; and the hydrocarbon substances inside, which have a lower boiling point than the outer shell, will decompose and volatilize before the polymer softens, thereby causing the microspheres to expand and support the foam matrix. The existing foaming system mainly controls the size of the pores by changing the number of hydroxyl groups in the polyether polyol, the type of foaming agent, catalyst, foaming agent, and filling material. Among them, the method of changing the filler is the simplest and most stable. For example, Liu Xu of Zhejiang Huafeng New Materials Company currently uses heat-expandable microspheres to enhance the polyurethane foam matrix (CN101486801B). This method is simple, easy to operate, and low-cost. A foaming density of 0.28 to 0.32 g / cm 3 Available polyurethane elastomer sole material, the apparent density can be 0.28g / cm 3 , tensile strength is 4.3MPa, and hardness ShoreC is 72; however, the invention adopts the method of simply adding expandable beads, which brings more closed-cell structures to the system and lacks some exhaust and ventilation processes. The foam produced by this process has a higher hardness, that is, the sole is stiff and the rebound is weak in leisure environments such as slow walking, the corresponding energy absorption efficiency will be greatly reduced, and the comfort is poor.
[0006] Shear thickening fluid (STF) is a stress-sensitive material that uses colloidal particles to disperse and form a suspension. At a high shear rate, the particles of the suspension are coupled to each other and enter a closed trajectory to form a particle cluster. At this time, the particle concentration of the particle cluster is relatively large. When the system is sheared, the energy consumed increases, resulting in an increase in viscosity. The change in viscosity is used to achieve a highly nonlinear change in mechanical properties. Adding shear thickening materials to polyurethane foam can make the system viscosity variable and dissipate energy from the applied stress, thereby achieving enhancement. For example, Liu Xiao from Jiangnan University used shear thickening materials to enhance and modify polyurethane foam, and introduced the stress response characteristics of shear thickening materials into the composite material system, achieving an 80-90% increase in specific strength and specific energy absorption; however, in this report, the shear thickening material is in direct contact with the polyurethane foam material, and the alcohol group therein will destroy the molding of the polyurethane foam to a certain extent, increase the number of open cells and enlarge the pore size, and the foam is prone to rupture and failure. Regarding shear thickening fluid, there are also reports. Liu Xing from Tianjin Polytechnic University used homemade shear thickening fluid to prepare a series of STF capsule / polyurethane foam composite materials. His research showed that adding an appropriate amount of STF capsules can improve the comprehensive mechanical properties of the composite materials by more than 1 times. The purpose of using shear thickening fluid capsules in this report is to more conveniently apply shear thickening fluid. The STF capsule content reaches 30%, and the density of the corresponding foam increases significantly. The material is harder, which is not conducive to the application of shoe materials.
[0007] In summary, it is necessary to prepare polyurethane composite materials for shoes that have moderate mechanical properties and good energy absorption efficiency while maintaining a low density. Summary of the invention
[0008] In view of the above problems existing in the prior art, the present invention provides a method for preparing a polyurethane composite material for multi-way comfort footwear. The present invention uses solid ball shear thickening liquid capsules and hollow ball expandable beads to enhance the virtual and real phases of polyurethane foam. The reaction can be carried out at room temperature, which is conducive to large-scale preparation, and the raw materials are cheap and easy to obtain. The method uses expandable beads as hollow balls, which are hollow inside. After being heated and expanded in the foaming stage, they form expanded balls of stable size, which can exist as closed cells in the foam system, regulate the open and closed cell ratio, and are conducive to bearing loads.
[0009] The preparation method of the present invention effectively controls the proportion of material usage, and performs two-phase reinforcement of solid spheres and hollow spheres while ensuring that the density of the foam material remains basically unchanged, thereby improving the mechanical properties of the foam composite material and enhancing its energy absorption efficiency, and improving stress sensitivity, having a certain damping effect on the external load. At the same time, the reaction occurs at room temperature and can be cured at room temperature, thereby reducing energy consumption and being conducive to large-area application.
[0010] The present invention provides a method for preparing a polyurethane composite material for multi-use comfort shoes, comprising:
[0011] (1) Material A (polyether polyol), foaming catalyst, deionized water, anti-yellowing agent, gel catalyst, hollow spherical expandable beads and solid spherical shear thickening liquid capsules are mixed uniformly in a predetermined ratio to obtain a matrix preform.
[0012] (2) The matrix prefabricated material and material B (isocyanate) are mixed uniformly in a predetermined ratio, mechanically stirred for 6-10 seconds, and then quickly poured into a mold to flow evenly, and then pressed. After 2-5 minutes of foaming, the mold is opened and the material is taken out, and then aged at 20-28 degrees Celsius for 20 minutes to obtain a polyurethane composite material for shoe materials.
[0013] In one embodiment, the shear thickening liquid is first prepared into solid spherical shear thickening liquid capsules, which are then dried at room temperature for later use.
[0014] In one embodiment, the method for preparing the shear thickening liquid capsules is to use a surfactant, a sodium alginate solution, and a calcium chloride solution to prepare the shear thickening liquid capsules.
[0015] In one embodiment, a method for preparing a homemade shear thickening fluid comprises mixing ethylene glycol (PEG) and silicon dioxide (SiO 2 ) powders were mixed, stirred thoroughly and placed in a vacuum drying chamber at 25° C. for 24 hours to remove bubbles, thereby obtaining a shear thickening liquid.
[0016] In one embodiment, the surfactant used in the preparation of the shear thickening liquid capsule is a Span series, the addition amount is 10-30%, the concentration of the sodium alginate solution is 5-10 mg / mL, and the concentration of the calcium chloride solution is 10-20 mg / mL.
[0017] In one embodiment, the preparation method of shear thickening fluid capsules adopts the method of Xing Liu of Tianjin Polytechnic University to prepare shear thickening fluid capsules. The specific steps are: dripping the prepared shear thickening fluid (STF) into liquid paraffin to form an oil-in-water emulsifier, stirring at 25°C for 30 minutes; adding a hydrophilic surfactant to the sodium alginate solution and mixing thoroughly, and then slowly adding the oil-in-water emulsifier; mixing at 25°C for 20 minutes to form a water-in-oil-in-water multiple emulsion. The water-in-oil-in-water multiple emulsion is sucked into a small diameter syringe. The syringe is set as a microinjection pump with a driving speed of 8-13μL / min, and is pushed into the prepared calcium chloride solution to form spherical droplets. Rinse with deionized water and dry at room temperature.
[0018] In one embodiment, the mass proportions of the components in step (1) are 100 parts of material A, 2 to 4 parts of foaming catalyst, 0.3 to 0.4 parts of deionized water, 3 to 5 parts of anti-yellowing agent, 0.15 to 0.2 parts of gel catalyst, 1 to 5 parts of hollow spherical expandable beads, and 1 to 5 parts of solid spherical shear thickening liquid capsules.
[0019] In one embodiment, in step (1), 1 to 3 parts of hollow spherical expandable beads and 1 to 3 parts of solid spherical shear thickening liquid capsules are used.
[0020] In one embodiment, in step (1), 3 parts of hollow spherical expandable beads and 3 parts of solid spherical shear thickening liquid capsules are used.
[0021] In one embodiment, the hollow spherical expandable beads (or heat-foamable microspheres, expandable foaming microspheres, etc.) used in step (1) are one or more of the EXPANCEL series, DE series, UM115 series, and UM116 series, with an initial particle size of 6 to 10 μm and a minimum foaming temperature of 80 to 85°C.
[0022] In one embodiment, the mass fraction of material B in step (2) is 60 to 75 parts.
[0023] In one embodiment, the mass fraction of material B in step (2) is 70 parts.
[0024] In the present invention, material A and material B can be the AB materials of existing polyurethane soft foam; for example, the polyether polyol-conventional ratio-polyether polyol for insoles mentioned in the "Polyurethane Foam Handbook".
[0025] In one embodiment, material A is one or more of polyether diols or polyether triols.
[0026] In one embodiment, material B is one or more of isocyanate or liquefied diphenylmethane diisocyanate.
[0027] In the present invention, the AB material, foaming catalyst, anti-yellowing agent, gelling catalyst, etc. used in the preparation process of polyurethane foam are all conventional raw materials for preparing polyurethane foam, and can be purchased commercially. For example, the foaming catalyst and gelling catalyst can be purchased from Huafeng, Huntsman, Momentive, Qiqi and Chen brands.
[0028] In one embodiment, the foaming catalyst, the anti-yellowing agent, and the gelling catalyst are purchased from China Huafeng Group.
[0029] In one embodiment, the anti-yellowing agent used is one or more of HN130, HN150, and C-21.
[0030] In the present invention, the mass fraction of material B needs to be strictly controlled, otherwise the foaming reaction will not be thorough and the curing effect will be poor. Foaming time is also a key point. If the mixing time is insufficient, the foaming may not be complete or even completely absent if it is sent to the pressure mold for foaming before sufficient contact. If the mixing time is too long, foaming will begin before it is transferred to the mold, resulting in a product with too large pores and a reduced yield. The foaming temperature also has a significant effect on the pores. The mixing reaction of material A and material B will release heat equivalent to the degree of reaction. The expandable beads expand using the heat at this stage, which means that the ratio of material A to material B directly affects the expansion rate of the expandable beads.
[0031] In the present invention, when the AB materials react, the ambient temperature affects the reaction efficiency and speed of both. When the temperature is lower than 15°C, the reaction efficiency and speed of both are greatly affected. Preferably, the working environment is maintained at about 25°C.
[0032] The second object of the present invention is to provide a polyurethane composite material for multi-use comfort shoes prepared according to the above method.
[0033] In the present invention, the shear thickening liquid is made into capsules and doped into the system in the form of solid balls, which improves the problem of interface compatibility and avoids direct contact between excessive alcohol substances and isocyanate, thereby damaging the foaming effect; unlike Liu Xing of Tianjin Polytechnic University, the purpose of using shear thickening liquid capsules in the present invention is to better retain the shear thickening characteristics. At the same time, it is dispersed in the foam elastomer in the form of solid balls, and the local stress-strain sensitivity is enhanced, which provides a stronger rebound and support effect on a macro scale during high-speed ball loading. The shear thickening performance of STF capsules and the excellent buffering performance of polyurethane foam are the reasons for the improvement of the mechanical properties of composite materials. In addition, the present invention synergizes the shear thickening liquid capsules with expandable beads in the polyurethane foam, and the density of the expandable beads can be used to partially offset the adverse effects of the shear thickening liquid capsules.
[0034] In the present invention, by adding hollow spherical expandable beads and solid spherical shear thickening liquid capsules, the closed cell rate in the pore structure is increased, and the energy absorption effect of the composite material is improved. Although the solid spherical shear thickening liquid capsules increase the density of the composite material to a certain extent, adding a proper amount can not only enhance the effect of energy absorption and resistance reduction, but also enrich bubbles to form pore clusters. The hollow spherical expandable beads are distributed on the pore walls of the polyurethane foam to form micropores, which indirectly reduces the size of the pores formed by foaming, and more dense foam is conducive to the improvement of mechanical properties. In addition, the introduction of hollow spheres also reduces the density of the composite material.
[0035] The polyurethane foam of the present invention can be applied to the field of energy-absorbing shoe materials.
[0036] The present invention also provides the application of the polyurethane composite material for multi-way comfortable footwear, specifically for making multi-way comfortable footwear, and providing matching support strength and shock absorption effect for the needs of walking, jogging and other sports in daily life. At the same time, the universality of age and body shape is improved. When the elderly use this shoe material, the presence of the hollow balls reduces the density of the composite material, and at the same time, the existence of the closed-cell structure in the system enhances the effect of energy absorption and shock absorption. The solid ball shear thickening liquid capsule produces a smaller viscosity change when responding to low-speed loads, and has less stimulation to the soles of the feet. When people with heavier weight use this shoe material, the solid ball shear thickening liquid capsule can provide better support effect for the composite material system, avoid stress collapse, and extend the service life.
[0037] Advantages and effects of the present invention:
[0038] 1. The present invention introduces solid ball shear thickening liquid capsules. The shear thickening liquid has a damping effect under stress conditions, which can change the viscosity of the system to achieve energy absorption and dissipation. In addition, the external calcium alginate shell can also absorb impact energy, thereby enhancing the strength of the STF capsule. Therefore, due to the damping characteristics of the STF capsule in terms of mechanical force, the overall composite material can be made to reflect stress sensitivity. In the present invention, the introduction of shear thickening liquid capsules can adjust the strain rate effect and change the pore structure (there are small pores on the pores); through STF capsule-solid sphere, expandable bead microsphere-hollow sphere, the role of the solid matrix and the pore structure is fully utilized to achieve the ultra-comfort of casual shoes, which are suitable for all kinds of fast walking shoes and slow walking shoes.
[0039] 2. The present invention enhances the elasticity and mechanical strength of the matrix through hollow spherical expandable beads, which can partially replace water as a foaming agent, thereby eliminating foam collapse to a certain extent. When the expandable beads are heated and expanded, the particle size can reach 10-20 μm, which can achieve a stable pore size. At the same time, due to its closed form, the open and closed porosity of the foam system can be adjusted, thereby improving the energy absorption efficiency and compressive strength of the overall composite material.
[0040] 3. The two-phase reinforced polyurethane foam composite material of the present invention has an energy absorption efficiency several times higher than that of conventional polyurethane foam, and the energy absorption can reach 52.4489KJ / m 3 -57.2162KJ / m 3 At the same time, the compression strength reaches 3.0888MPa-3.7076MPa, and the apparent density can be maintained at 0.311g / cm 3 -0.351g / cm 3 The apparent density of polyurethane for shoe materials is usually 0.2-0.4 g / cm 3 The apparent density of this patent is maintained at 0.3-0.35 g / cm 3Within this range, it can provide a comfortable feeling for the foot, which is neither light nor heavy, and has the feel of a shoe but is not cumbersome. It can provide strong plantar support and cushioning performance in daily leisure and competitive sports scenes, protect the knees, and maximize the benefits of exercise. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It is a schematic diagram of the cross section of the composite material, wherein 1-1 is a solid spherical shear thickening liquid capsule, and 1-2 is a hollow spherical expandable bead.
[0042] Figure 2 The SEM scanning image of the composite material. Specific implementation plan
[0043] Determination method:
[0044] 1. Apparent density determination method: According to GB / T6343-1995 Determination of apparent (volume) density of foam plastics and rubber, cut into samples with a size of 20×20×10mm, accurately measure the length, width and height of the sample, accurate to 0.02mm. Then use an electronic balance to accurately weigh the sample mass, requiring an accuracy of 0.0001g, and then calculate the apparent density.
[0045] 2. Compression strength determination method: According to the standard of GB / T6669-2008 for permanent deformation of slow-rebound foam polymer materials, the universal strength testing machine is used for testing, and the compression strength is obtained by data analysis of the performance curve image of the test results.
[0046] 3. Energy absorption measurement method: The energy absorption is calculated by analyzing the performance curve image of the test results using a universal strength testing machine according to the GB / T6669-2008 standard for permanent compression deformation of slow-rebound foam polymer materials.
[0047] Example 1
[0048] The polyurethane composite material for multi-use comfort shoes and the preparation method thereof are implemented according to the following steps:
[0049] (1) Self-made shear thickening fluid, the specific preparation method is: take PEG and SiO with a mass ratio of 3:1 2 , and then placed in a vacuum drying chamber at 25°C for 24 hours after being fully stirred to remove bubbles, thereby obtaining a shear thickening liquid.
[0050] (2) preparing shear thickening liquid capsules according to the literature method and drying them at room temperature for later use;
[0051] Specifically, the shear thickening fluid capsules were prepared using the method of Xing Liu from Tianjin Polytechnic University. The specific steps are as follows: drip the homemade shear thickening fluid (STF) into liquid paraffin to form an oil-in-water emulsifier, and stir at 25°C for 30 minutes. Add a hydrophilic surfactant to the sodium alginate solution and mix thoroughly, then slowly add the oil-in-water emulsifier. Mix at 25°C for 20 minutes to form a water-in-oil-in-water multiple emulsion. Aspirate the water-in-oil-in-water multiple emulsion into a small diameter syringe. The syringe is set as a microinjection pump with a driving speed of 10μL / min, and pushes into the prepared calcium chloride solution to form spherical droplets. Rinse with deionized water and dry at room temperature.
[0052] (3) 100 parts of material A (polyether polyol), 2 parts of foaming catalyst, 0.36 parts of deionized water, 3 parts of anti-yellowing agent, 0.19 parts of gel catalyst, 3 parts of hollow spherical expandable beads and 3 parts of solid spherical shear thickening liquid capsules are mixed uniformly in proportions by mass to obtain a matrix preform;
[0053] (4) The matrix prefabricated material and material B (isocyanate) are mixed uniformly in a mass ratio of 100:70, mechanically stirred for 6-10 seconds, and quickly poured into a mold to flow evenly, and then pressed. The mold is opened and the material is taken out 2 minutes after the foaming is completed, and the matrix material is matured at 20-28 degrees Celsius for 20 minutes to obtain the matrix material.
[0054] The obtained sample has smooth surface, uniform pores, small molding shrinkage, and an apparent density of 0.311 g / cm 3 , compression strength 3.0888MPa, energy absorption 57.2162KJ / m 3 . This is a group of relatively ideal effects in the embodiments of this patent, maintaining a moderate apparent density while achieving the maximum energy absorption effect.
[0055] Figure 1 The cross-sectional diagram of the prepared composite material is shown in Figure 2. The hollow spherical expandable beads and the solid spherical shear thickening liquid capsules are evenly distributed in the polyurethane matrix, and the apparent density of the matrix is synergistically controlled, which enhances its compression strength and energy absorption efficiency without increasing the apparent density too much.
[0056] Figure 2The SEM scanning image of the polyurethane composite material prepared in this embodiment characterizes the internal pore structure. Through observation, it can be found that the addition of hollow spherical expandable beads has a great influence on the pore morphology. After adding hollow spherical expandable beads, it is equivalent to introducing impurity nuclei into the system, which is conducive to the adsorption of gas to form fine pores. When it is distributed on the pore wall, the pore wall is concave. This concave forms a small through hole. When a low-speed load is applied, the gas has enough time to escape from the through hole. When the load is evacuated, it can absorb air to restore the shape. When a high-speed load is applied, the gas has no time to escape, which can provide a good energy absorption and shock absorption effect for the shoe material. The appropriate addition of hollow spherical expandable beads can not only increase the pore density, but also make the pore wall thicker. When facing long-term or repeated loads, its durability is higher.
[0057] The composite material prepared in Example 1 can ideally meet the requirements of multi-use comfort shoes, that is, it can correspond to a variety of usage scenarios and show different usage effects. For example, in jogging scenarios, the shoe material can moderately exhaust air, absorb energy and reduce shock to avoid knee damage; in competitive sports scenarios, it can instantly lock air, provide high rebound performance, and help increase speed. This embodiment relatively perfectly meets the realistic standard of one shoe for multiple uses, taking into account both density and energy absorption effects.
[0058] Example 2
[0059] The polyurethane composite material for multi-use comfort shoes and the preparation method thereof are implemented according to the following steps:
[0060] (1) As shown in step (1) of Example 1, a shear thickening liquid is prepared and cooled to room temperature for later use;
[0061] (2) As shown in step (2) of Example 1, shear thickening liquid capsules were prepared and dried at room temperature for later use;
[0062] (3) 100 parts of material A (polyether polyol), 2 parts of foaming catalyst, 0.36 parts of deionized water, 3 parts of anti-yellowing agent, 0.19 parts of gel catalyst, 1 part of hollow spherical expandable beads and 3 parts of solid spherical shear thickening liquid capsules are mixed uniformly in proportions by mass to obtain a matrix preform;
[0063] (4) The matrix prefabricated material and material B (isocyanate) are mixed uniformly in a mass ratio of 100:70, mechanically stirred for 6-10 seconds, and quickly poured into a mold to flow evenly, and then pressed. The mold is opened and the material is taken out 2 minutes after the foaming is completed, and the matrix material is matured at 20-28 degrees Celsius for 20 minutes to obtain the matrix material.
[0064] The obtained sample has smooth surface, uniform pores, small molding shrinkage, and an apparent density of 0.351g / cm 3 , compression strength 3.7067MPa, energy absorption 52.4489KJ / m3 .
[0065] Compared with Example 1, the amount of hollow spherical expandable beads added is reduced, the apparent density is slightly increased, and the energy absorption unit is reduced, and the energy absorption efficiency is slightly reduced. Example 2 can also be applied to multi-way comfort shoe materials, only compared with Example 1, Example 1 is better.
[0066] Example 3
[0067] The polyurethane composite material for shoes and the preparation method thereof are implemented according to the following steps:
[0068] (1) As shown in step (1) of Example 1, a shear thickening liquid is prepared and cooled to room temperature for later use;
[0069] (2) As shown in step (2) of Example 1, shear thickening liquid capsules were prepared and dried at room temperature for later use;
[0070] (3) 100 parts of material A (polyether polyol), 2 parts of foaming catalyst, 0.36 parts of deionized water, 3 parts of anti-yellowing agent, 0.19 parts of gel catalyst, 3 parts of hollow spherical expandable beads and 5 parts of solid spherical shear thickening liquid capsules were mixed uniformly in proportions by mass to obtain a matrix preform;
[0071] (4) The matrix prefabricated material and material B (isocyanate) are mixed uniformly in a mass ratio of 100:70, mechanically stirred for 6-10 seconds, and quickly poured into a mold to flow evenly, and then pressed. The mold is opened and the material is taken out 2 minutes after the foaming is completed, and the matrix material is matured at 20-28 degrees Celsius for 20 minutes to obtain the matrix material.
[0072] The obtained sample has smooth surface, uniform pores, small molding shrinkage, and an apparent density of 0.912g / cm 3 , compression strength 4.2586MPa, energy absorption 19.9390KJ / m 3 .
[0073] Compared with Example 1, the amount of solid spherical shear thickening liquid capsules added is increased. Since the density of the shear thickening liquid capsules is much greater than that of the foam itself, when the amount of shear thickening gel added is relatively large, the density of the matrix is more affected, and due to its position in the foam matrix, the effective foaming space is reduced, and the pores are the core of the foam material for energy absorption and shock reduction, which ultimately leads to a phenomenon of reduced energy absorption efficiency.
[0074] Comparative Example 1:
[0075] The preparation of the polyurethane composite material for shoe materials without adding hollow spherical expandable beads and solid spherical shear thickening liquid capsules is specifically carried out according to the following steps:
[0076] (1) As shown in step (1) of Example 1, a shear thickening liquid is prepared and cooled to room temperature for later use;
[0077] (2) As shown in step (2) of Example 1, shear thickening liquid capsules were prepared and dried at room temperature for later use;
[0078] (3) 100 parts of material A (polyether polyol), 2 parts of foaming catalyst, 0.36 parts of deionized water, 3 parts of anti-yellowing agent, and 0.19 parts of gel catalyst are mixed uniformly in proportions by mass to obtain a matrix prefabricated material;
[0079] (4) The matrix prefabricated material and material B (isocyanate) are mixed uniformly in a mass ratio of 100:70, mechanically stirred for 6-10 seconds, and quickly poured into a mold to flow evenly, and then pressed. The mold is opened and the material is taken out 2 minutes after the foaming is completed, and the matrix material is matured at 20-28 degrees Celsius for 20 minutes to obtain the matrix material.
[0080] The obtained sample has smooth surface, uniform pores, small molding shrinkage, and an apparent density of 0.258cm 3 , compression strength 2.7268MPa, energy absorption 24.754KJ / m 3 The comparative example prepared a blank substrate, retaining only the polyurethane foam part, without adding other synergistic substances. This material has limited energy absorption effect, and at the same time, the weakness of the polyurethane foam itself is not eliminated, and stress softening is prone to occur under long-term load, shortening the service life.
[0081] Comparative Example 2
[0082] The polyurethane composite material for shoes and the preparation method thereof are implemented according to the following steps:
[0083] (1) As shown in step (1) of Example 1, a shear thickening liquid is prepared and cooled to room temperature for later use;
[0084] (2) As shown in step (2) of Example 1, shear thickening liquid capsules were prepared and dried at room temperature for later use;
[0085] (3) 100 parts of material A (polyether polyol), 2 parts of foaming catalyst, 0.36 parts of deionized water, 3 parts of anti-yellowing agent, 0.19 parts of gel catalyst, 0 parts of hollow spherical expandable beads and 3 parts of solid spherical shear thickening liquid capsules are mixed uniformly in proportions by mass to obtain a matrix preform;
[0086] (4) The matrix prefabricated material and material B (isocyanate) are mixed uniformly in a mass ratio of 100:70, mechanically stirred for 6-10 seconds, and quickly poured into a mold to flow evenly, and then pressed. The mold is opened and the material is taken out 2 minutes after the foaming is completed, and the matrix material is matured at 20-28 degrees Celsius for 20 minutes to obtain the matrix material.
[0087] The obtained sample has a smooth surface, concentrated pore distribution, small molding shrinkage, and an apparent density of 0.76g / cm 3 , compression strength 3.5924MPa, energy absorption 25.0071KJ / m 3 On the basis of the blank matrix, only solid spherical shear thickening liquid capsules are added, whose density is much greater than that of the polyurethane foam material itself, which increases the apparent density of the overall composite material. Although the compression strength is enhanced, the increase in weight increases the load for competitive sports applications, and as a daily casual shoe material, its exhaust effect is not improved, but the increase in weight load has certain restrictions on the age of the audience.
[0088] Comparative Example 3
[0089] The polyurethane composite material for shoe material and the preparation method thereof are implemented according to the following steps:
[0090] (1) As shown in step (1) of Example 1, a shear thickening liquid is prepared and cooled to room temperature for later use;
[0091] (2) As shown in step (2) of Example 1, shear thickening liquid capsules were prepared and dried at room temperature for later use;
[0092] (3) 100 parts of material A (polyether polyol), 2 parts of foaming catalyst, 0.36 parts of deionized water, 3 parts of anti-yellowing agent, 0.19 parts of gel catalyst, 3 parts of hollow spherical expandable beads and 0 parts of solid spherical shear thickening liquid capsules are mixed uniformly in a ratio of mass to obtain a matrix preform;
[0093] (4) The matrix prefabricated material and material B (isocyanate) are mixed uniformly in a mass ratio of 100:70, mechanically stirred for 6-10 seconds, and quickly poured into a mold to flow evenly, and then pressed. The mold is opened and the material is taken out 2 minutes after the foaming is completed, and the matrix material is matured at 20-28 degrees Celsius for 20 minutes to obtain the matrix material.
[0094] The obtained sample has smooth surface, uniform pores, small molding shrinkage, and an apparent density of 0.211g / cm 3 , compression strength 2.037MPa, energy absorption 23.5864KJ / m 3 Since only expandable beads are added, the closed cell rate increases, the density of the composite material is greatly reduced, and the compression strength is reduced. The adaptability to competitive sports scenes decreases, the scope of application scenarios is narrowed, and the ideal requirement of one shoe for multiple uses is not met.
[0095] Comparative Example 4
[0096] The polyurethane composite material for shoes and the preparation method thereof are implemented according to the following steps:
[0097] (1) As shown in step (1) of Example 1, a shear thickening liquid is prepared and cooled to room temperature for later use;
[0098] (2) As shown in step (2) of Example 1, shear thickening liquid capsules were prepared and dried at room temperature for later use;
[0099] (3) 100 parts of material A (polyether polyol), 2 parts of foaming catalyst, 0.36 parts of deionized water, 3 parts of anti-yellowing agent, 0.19 parts of gel catalyst, 3 parts of hollow spherical expandable beads and 3 parts of solid spherical shear thickening liquid capsules are mixed uniformly in proportions by mass to obtain a matrix preform;
[0100] (4) The matrix prefabricated material and material B (isocyanate) are mixed uniformly in a mass ratio of 100:75, mechanically stirred for 6-10 seconds, and then quickly poured into a mold to flow evenly, and then pressed. After 2 minutes of foaming, the mold is opened and the material is taken out, and then aged at 20-28 degrees Celsius for 40 minutes to obtain the matrix material.
[0101] The surface of the sample was sunken, the inside of the pores was partially collapsed and yellowed, and it felt rough. The apparent density was 0.573 g / cm 3 , compression strength 4.037MPa, energy absorption 29.3762KJ / m 3 .
[0102] Compared with Example 1, this embodiment increases the addition ratio of material B. The addition amount of material B determines the content of the hard segment. When material B increases, the hardness of the foam matrix increases, the difficulty of foaming increases, and the density and compression strength increase. At the same time, due to the relative excess of material B, the reaction with water is enhanced, causing the gel reaction speed to fail to keep up with the foaming reaction speed, which is easy to cause bubble collapse. At the same time, due to the extended aging time, heartburn will occur. Under this ratio, the pore structure is severely damaged, the energy absorption effect is greatly reduced, and the appearance and use requirements cannot be met.
[0103] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing a polyurethane composite material for multi-use comfort shoes, characterized in that: include: (1) mixing the polyether polyol of material A, a foaming catalyst, deionized water, an anti-yellowing agent, a gel catalyst, hollow spherical expandable beads and solid spherical shear thickening liquid capsules in a predetermined ratio to obtain a matrix preform; (2) The matrix prefabricated material and the B material isocyanate are mixed uniformly in a predetermined ratio, mechanically stirred for 6-10 seconds, and then quickly poured into a mold to make it flow evenly, and then pressed. After 2-5 minutes of foaming, the mold is opened to remove the material, and the material is aged at 20-28 degrees Celsius to obtain a composite material; The mass fractions of the components in step (1) are: 100 parts of material A, 2 to 4 parts of a foaming catalyst, 0.3 to 0.4 parts of deionized water, 3 to 5 parts of an anti-yellowing agent, and 0.15 to 0.2 parts of a gel catalyst; In step (1), 1 to 3 parts of hollow spherical expandable beads and 3 parts of solid spherical shear thickening liquid capsules are added; in step (2), the matrix prefabricated material and material B are evenly mixed in a mass ratio of 100:
70.
2. The preparation method according to claim 1, characterized in that: The method for preparing solid ball shear thickening liquid capsules comprises the following steps: using a surfactant, a sodium alginate solution and a calcium chloride solution to prepare the shear thickening liquid capsules.
3. The preparation method according to claim 1, characterized in that: The hollow spherical expandable beads used in step (1) are one or more of EXPANCEL series, DE series, UM115 series, and UM116 series, with an initial particle size of 6 to 10 μm and a minimum foaming temperature of 80 to 85° C.
4. The preparation method according to claim 1, characterized in that: Material A is one or more of polyether diol or polyether triol; material B is one or more of isocyanate or liquefied diphenylmethane diisocyanate.
5. A polyurethane composite material for shoe materials prepared according to any one of claims 1 to 4.
6. The use of the polyurethane composite material for shoe materials according to claim 5, characterized in that: The application is in the field of energy absorbing footwear materials, including multi-way comfort footwear materials.
Citation Information
Patent Citations
Low density polyurethane micropore elastomer added with thermal foamable microsphere and preparation thereof
CN101486801B